2018
DOI: 10.1002/adfm.201707582
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled pH‐Sensitive Fluoromagnetic Nanotubes as Archetype System for Multimodal Imaging of Brain Cancer

Abstract: Fluoromagnetic systems are recognized as an emerging class of materials with great potential in the biomedical field. Here, it is shown how to fabricate fluoromagnetic nanotubes that can serve as multimodal probes for the imaging and targeting of brain cancer. An ionic self-assembly strategy is used to functionalize the surface of synthetic chrysotile nanotubes with pH-sensitive fluorescent chromophores and ferromagnetic nanoparticles. The acquired magnetic properties permit their use as contrast agent for mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Here, pH 5 was used to mimic the real acidic tumor microenvironment. [ 44 ] As shown in Figure S14a (Supporting Information), comparable O 2 generation capacity was seen between pH 7.4 and 5.0, suggesting the applicability of Au@Rh‐CM to physiological pH. It is worth mentioning that the elevated temperature as a result of mild/moderate photothermal effect of Au@Rh‐CM (Figure 1h) might facilitate the catalytic decomposition of H 2 O 2 to O 2 .…”
Section: Methodsmentioning
confidence: 76%
“…Here, pH 5 was used to mimic the real acidic tumor microenvironment. [ 44 ] As shown in Figure S14a (Supporting Information), comparable O 2 generation capacity was seen between pH 7.4 and 5.0, suggesting the applicability of Au@Rh‐CM to physiological pH. It is worth mentioning that the elevated temperature as a result of mild/moderate photothermal effect of Au@Rh‐CM (Figure 1h) might facilitate the catalytic decomposition of H 2 O 2 to O 2 .…”
Section: Methodsmentioning
confidence: 76%
“… 37 We employ synthetic chrysotile NTs as nanoscintillators because according to the literature, these nanostructures are highly biocompatible particles that can be prepared in aqueous solution under hydrothermal conditions in the presence of Mg and Si precursors. 38 With the chemical formula Mg 3 Si 2 O 5 (OH) 4 , chrysotile is a layered silicate having alternating layers of silica, SiO 2 , and brucite, Mg(OH) 2 ( Figure 1 d), 39 which are wrapped up giving rise to a tubular habit ( Figure 1 c). By tuning the reaction time, the size distribution of the NTs can be controlled to a certain extent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Interestingly, one study demonstrated that fluoromagnetic nanotubes, administered by IV injection, crossed the blood brain barrier and located to the tumor site in Nod/Scid mice. [ 132 ]…”
Section: Nanomedicines Designed For Targeting and Treatment Of Cancersmentioning
confidence: 99%